Proteomics Analysis of Hydatigera taeniaeformis Metacestode Stage - Guo, Xiaola (Frontiers in Veterinary Science, 2020)
Hydatigera taeniaeformis (H. taeniaeformis) is one of the most robust of tapeworm parasites that is widely distributed around the world. Information of proteins of H. taeniaeformis has not previously been reported. Using liquid chromatography tandem-mass spectrometry (LC–MS/MS) analysis, the proteome of H. taeniaeformis metacestode was proﬁled and a total of 408 proteins were identiﬁed. Of these, 26.5% (108/408) were annotated to be associated with metabolic pathways. Consistently, Gene Ontology analysis showed that those identified proteins were mainly classified into metabolic process of the biological processes. A set of metabolic enzymes, including Fructose-1,6-bisphosphate aldolase, enolase, Glucan phosphorylase, and phosphoenolpyruvate carboxykinase, were abundant in H. taeniaeformis metacestodes. In addition, some rare but interesting proteins like antigens (such as tegument protein and Antigen B) were identified. The two recombinant proteins of tegument protein and Antigen B were well recognized by the sera from the H. taeniaeformis-infected mice. The H. taeniaeformis metacestode proteome might help to find new candidates for the immunodiagnosis and vaccine development and provide valuable information on H. taeniaeformis biology.